The design and application of a government environmental information disclosure index in China. (20th November 2018) - Kosajan, Vorada; Chang, Miao; Xiong, Xueying; Feng, Yan; Wang, Shiwen
Abstract: With the development of Big Data, governments with abundant public data have realized the importance of information disclosure. Governments of the world have paid more attention to intelligent data analysis for scientific decision-making. Environmental information disclosure is not only an important environmental management tool, but also a significant subfield of government information disclosure. Currently, over 60 countries and regions around the world have established their own government information disclosure systems, and the related theoretical research has advanced considerably. However, there are such large numbers of problems during the development and implementation of the relevant information disclosure policies in developing countries. Environmental information disclosure would lead to significant beneficial impacts of practical significance relating to the protection of the public's right to know, participate, supervise, and improve the quality of environmental management in developing countries. The purpose of this study was to design a feasible system relating to government environmental information disclosure. This study is the first to apply the entire-array-polygon method in the context of environmental information disclosure evaluation. The results revealed that the average value of the government environmental information disclosure index for the 31 provinces was 0.25, indicating an overall level that was categorized as "general". None of the provinces was categorized as "excellent". The EAP method could be applied to government environmental information disclosure in both China and other developing countries. Graphical abstract: Image 1 Highlights: The relationship of Big Data and information disclosure were mentioned which enhanced the internationalism. The hierarchy is made of grading results from primary, secondary evaluation indicators and dimensions. The entire-array-polygon method was first applied in environmental information disclosure evaluations in China. Regional imbalance in environmental information disclosure were related to regional economy and pollution. Information identification and capture technology were suggested to be applied for automated evaluations in the future.